Disappearing organization?: reshaping the sociology of organizations - Besio, Cristina; Du Gay, Paul; Serrano-Velarde, Kathia (Sage, 2020)
This monograph showcases some recent developments in the sociology of organizations, mapping out the most productive relationships between current social scientific work on organizations and core theoretical and empirical concerns in the discipline of sociology.